The Value of a Statistical Injury: New Evidence from the Swiss Labor Market - Andreas Kuhn; Oliver Ruf (Swiss Journal of Economics and Statistics, 2013)
We study the monetary compensation for non-fatal accident risk in Switzerland using the number of accidents within cells defined over industry x skill-level of the job and capitalizing on the partial panel structure of our data. Our results show that using accident risk at a lower level of aggregation, using narrower samples of workers, and using the wage component that is specific to the firm all yield higher (i.e. more positive) estimates of risk compensation. However, we only find a statistically significant positive compensation for non-fatal accident risk for workers in jobs with the lowest skill-level. Our preferred estimate for this group of workers yields an estimate of about 35,000 Swiss francs per prevented injury per year.
Keywords: J17; J28; J31; 330; Compensating wage differentials; value of a statistical injury; risk measurement